Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan pada Adiwana Unagi States Ubud Bali - I Ketut Eli Sumerta; I Gede Restu Eko Putra (Universitas Triatma Mulya, 2025)
Leadership style and work motivation have an important role in creating employee performance in a company. This study was conducted to analyze the influence of leadership style and work motivation on employee performance at Adiwana Unagi Suites Ubud, Bali, this study aims to determine the partial and simultaneous influence between leadership style and work motivation on employee performance, to determine the influence of independent variables simultaneously on the dependent variable. The population in this study was 52 respondents. This study used quantitative and qualitative methods. Based on the results of the analysis, the results of the regression analysis showed that leadership style had a tvalue of 2,477 > ttable 1,676 and a significant value of 0.00 < 0.05 was obtained. It can be concluded that leadership style has a positive and significant partial effect on employee performance at Adiwana Unagi Suites Ubud, Bali. The results of the work motivation analysis have a tvalue of 2,386> ttable 1,676 and a significant value of 0,00 < 0,05 was obtained. It can be concluded that work motivation has a positive and significant partial effect on employee performance at Adiwana Unagi Suites Ubud, Bali. Simultaneously shown by the results of the Ftest obtained an Fcount value of 8,938 > Ftable 3,19 with a significant value of 0,00 > 0,05. It can be concluded that leadership style and work motivation have a positive and significant influence on employee performance at Adiwana Unagi Suites Ubud, Bali.